Early-Childhood Social Reticence Predicts Brain Function in Preadolescent Youths During Distinct Forms of Peer Evaluation. (June 2016) - Jarcho, Johanna M.; Davis, Megan M.; Shechner, Tomer; Degnan, Kathryn A.; Henderson, Heather A.; Stoddard, Joel; Fox, Nathan A.; Leibenluft, Ellen; Pine, Daniel S.; Nelson, Eric E.
Social reticence is expressed as shy, anxiously avoidant behavior in early childhood. With development, overt signs of social reticence may diminish but could still manifest themselves in neural responses to peers. We obtained measures of social reticence across 2 to 7 years of age. At age 11, preadolescents previously characterized as high ( n = 30) or low ( n = 23) in social reticence completed a novel functional-MRI-based peer-interaction task that quantifies neural responses to the anticipation and receipt of distinct forms of social evaluation. High (but not low) social reticence in early childhood predicted greater activity in dorsal anterior cingulate cortex and left and right insula, brain regions implicated in processing salience and distress, when participants anticipated unpredictable compared with predictable feedback. High social reticence was also associated with negative functional connectivity between insula and ventromedial prefrontal cortex, a region commonly implicated in affect regulation. Finally, among participants with high social reticence, negative evaluation was associated with increased amygdala activity, but only during feedback from unpredictable peers.